2013
DOI: 10.1038/cmi.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

The shrimp IKK–NF-κB signaling pathway regulates antimicrobial peptide expression and may be subverted by white spot syndrome virus to facilitate viral gene expression

Abstract: The IκB kinases IKKα and IKKβ and the IKK-related kinases TANK-binding kinase 1 (TBK1) and IKKε are the master regulators of the NF-κB signaling pathway. Although this pathway has been extensively studied in mammals, less attention has been paid in crustaceans, which have significant economic value. Here, we report the cloning and functional studies of two IKK homologs, LvIKKβ and LvIKKε, from Pacific white shrimp, Litopenaeus vannamei. LvIKKβ and LvIKKε mRNAs are widely expressed in different tissues and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Our study showed that ivabradine was associated with the significant dephosphorylation of caspase 3 and BAX, indicating the anti-apoptotic effect of ivabradine in diabetic animals. In contrast, NF-κB was activated by ivabradine, and phosphorylated NF-κB would promote protein synthesis and thus inhibit apoptosis [ 37 ]. These results would provide additional evidences of anti-ischemic effect by ivabradine for diabetic setting, in line with previously published results confirming the cardioprotective effect by ivabradine for patients with ischemic heart disease [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that ivabradine was associated with the significant dephosphorylation of caspase 3 and BAX, indicating the anti-apoptotic effect of ivabradine in diabetic animals. In contrast, NF-κB was activated by ivabradine, and phosphorylated NF-κB would promote protein synthesis and thus inhibit apoptosis [ 37 ]. These results would provide additional evidences of anti-ischemic effect by ivabradine for diabetic setting, in line with previously published results confirming the cardioprotective effect by ivabradine for patients with ischemic heart disease [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…LvIAP3 were significantly knocked down by dsRNA-mediated gene silencing [33] ). In the gills of LvIAP1-or LvIAP3-silenced shrimp, the expression of WSSV VP28 was significantly higher than that of the dsGFP control group, suggesting that LvIAP1 and LvIAP3 may play protective roles in host defense against WSSV infection [34].…”
Section: Nka Nkcc1 Gene Expression and Ion Concentration After Lysozmentioning
confidence: 99%
“…Hence, we speculate that PmVRP15 is not universally associated with WSSV susceptibility in other populations besides the Thai population. Furthermore, there are extensive studies indicating that WSSV resistance and WSSV susceptibility in penaeid shrimps is synergic immune response regulated by many genes (Ghosh et al, 2011), such as anti-lipopolysaccharide factor (ALF), which plays a role in defense against WSSV (Liu et al, 2014;Wang et al ,2013), Penaeus monodon antiviral (PmAV), which presumably acts as an intermediate factor during antiviral reaction (Luo et al, 2003), and other antimicrobial peptides like penaeidin class 5 that protect shrimps at early infection of WSSV (Jeswin et al, 2013;Wang et al, 2013). Perhaps WSSV susceptibility Al Haq et al in G 8 and G 8iA can be marked with other considerable immune-related gene expression rather than PmVRP15.…”
Section: Fig 2 Cumulative Mortality Of P Monodon Fabricius In G 8 Amentioning
confidence: 99%